Mangrove Nurseries as an Effort for Rehabilitation and Optimizing the Functions of Coastal Ecosystem Areas in Bandar Khalifah District, Serdang Bedagai Regency, North Sumatra Province - Manurung, Vindy Rilani; Harahap, Zulham Apandy; Rangkuti, Ahmad Baiquni; Husaini, Hasbi; Peranginangin, Denny Pahwen (Talenta Publisher, 2022)
The coastal area of ​​Serdang Berdagai district, Bandar Khalifa sub-district, has a population of 25,857 people With 80% working as fishermen, which is still dominated by small-scale fishing, This coastal area has a high diversity of mangroves, However, based on a survey, the mangrove ecosystem in this location has begun to be damaged and competition with trawl fishing boats, damage and competition result in a decrease in the catch of small fishermen, so that the optimization of the ecological area needs to be done through the implementation of mangrove rehabilitation, nurseries and the application of fishing aids, with the aim of increasing the catch of fishermen, The approach method used demonstration and counseling methods, socialization of activities by delivering material to mitra in the form of sharing sessions, followed by field practice with mangrove nurseries carried out by the community service team, Ministry of Marine Affairs and Fisheries extension and fishing mitra POKMASWAS Elang Putih and fishermen group KUB Bina Usaha Mandiri